Leepike Ridge - Wilson, N. D. (Random House : c2007 : Scholastic, Inc., 2009)
While his widowed mother continues to search for him, eleven-year-old Tom, presumed dead after drifting away down a river, finds himself trapped in a series of underground caves with another survivor and a dog, and pursued by murderous treasure-hunters.